The A to Z of fantasy literature - Stableford, Brian M. (A to Z guide series, 2009)
Once upon a time all literature was fantasy, set in a mythical pastwhen magic existed, animals talked, and the gods took an active hand inearthly affairs. As the mythical past was displaced in Westernestimation by the historical past and novelists became increasinglypreoccupied with the present, fantasy was temporarily marginalizeduntil the late 20th century, when it enjoyed a spectacular resurgencein every stratum of the literary marketplace.